In vitro culture and genetic transformation of cabbage CV. 88 (Brassica oleracea var. capitata) - Siti Nur Hanani Zainol (2005., 2005)
An in vitro study was carried out to determine the effects of different concentrations of BAP on axillary shoots proliferation and adventitious shoots regeneration on shoot tip explants of Brassica oleracea var. capitata cultivar 88. The shoot tip explants were cultured in Murashige and Skoog (MS) medium supplemented with various levels of BAP to induce shoots proliferation. It was observed that BAP at 1.0 mg/L was optimum for shoot multiplication in cabbage cultivar 88 with 4.4 shoots formed per explant. A minimal inhibitory concentration study was also carried out to determine the minimum kanamycin concentration that give toxicity to the in vitro grown shoots. The shoot tip explants were cultured on MS medium supplemented with different concentrations of kanamycin. The best treatment of BAP obtained from experiment 1 was also added into the medium to induce shoor formation. It was observed that kanamycin at 30 mg/L gave the lowest percentage of dead cultures of 53.33% compared to other treatments. Meanwhile, kanamysin concentration at and above 100 mg/L gave 100% of dead cultures. An Agrobacterium-mediated transformation study was carried out to determine the optimum Agrobacterium dilution for transformation. The shoot tip explants were co-cultivated in different dilutions of Agrobacterium and were then cultured in MS medium supplemented with BAP (1.0 mg/L) and carbenicillin (500 mg/L). It was observed that Agrobacterium dilution of 10-7 gave the highest percentage of positive growth of shoots of 58.33%.
Project paper (B.S.Bi.) - Universiti Putra Malaysia, 2005.